Remittances Levels and Trends - Kunwar, Laxman Singh (Patan Pragya, 2021)
This paper attempts to describe remittances levels and trends at global, regional and national levels. Remittances are being global phenomenon and its impacts have been increased from local level to global economy of world. It has been one of the top issues to analyze and address employment and economy sectors of local to national economy of remittances receiving countries of worlds. The paper is based on secondary sources of information with aim of find level and trends of remittances from national to global levels. Remittances through migration phenomenon has shown the evidences of in reducing poverty levels of remittances receiving regions or countries but the use of remittances pattern differs from one community to other. Nationally and globally volume of remittances has been increased with compared to previous years.